2020
DOI: 10.1108/jfra-03-2020-0076
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital: mediator of board of directors’ effectiveness and adoption of International Financial Reporting Standards

Abstract: Purpose The purpose of this paper is twofold: to test whether intellectual capital mediates the relationship between board of directors’ effectiveness and adoption of International Financial Reporting Standards (IFRS) and to examine the contribution of the specific elements of intellectual capital and board of directors’ effectiveness to adoption of IFRS. Design/methodology/approach This study is cross-sectional. Usable questionnaires were received from 67 microfinance institutions (MFIs) that are members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 34 publications
6
30
0
Order By: Relevance
“…Firms whose employees are more qualified and have obtained higher degree qualifications will have better sustainability reporting practices than those without. The finding that human capital does matter for sustainability reporting practices is consistent with the findings for Tumwebaze et al (2021) who found that human capital contributes significantly to the adoption of IFRS. Further, this study findings on human capital and sustainability reporting practices are in line with the findings of Kaawaase et al (2020) whose correlation analysis results indicated that human capital is significantly associated with both financial and non-financial performance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Firms whose employees are more qualified and have obtained higher degree qualifications will have better sustainability reporting practices than those without. The finding that human capital does matter for sustainability reporting practices is consistent with the findings for Tumwebaze et al (2021) who found that human capital contributes significantly to the adoption of IFRS. Further, this study findings on human capital and sustainability reporting practices are in line with the findings of Kaawaase et al (2020) whose correlation analysis results indicated that human capital is significantly associated with both financial and non-financial performance.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Bananuka (2020) found that structural capital is significantly correlated to internet financial reporting using evidence from Uganda. Tumwebaze et al (2021) found that structural capital contribute significantly to adoption of IFRS among Uganda's MFI.…”
Section: H2: Human Capital Has a Positive Effect On Sustainability Reporting Practicesmentioning
confidence: 98%
See 1 more Smart Citation
“…First, this study contributes to perception-based studies on sustainability reporting (e.g. Tauringana, 2021a;Tumwebaze et al, 2021;Thoradeniya et al, 2015). Perception-based studies document the direct managerial motivations for the improved SPD, unlike those panel data studies that rely on information whose intention of its inclusion in a report is not known.…”
Section: Introductionmentioning
confidence: 97%
“…Available perception-based studies (e.g. Tauringana, 2021a;Tumwebaze et al, 2021;Thoradeniya et al, 2015) do not investigate the impact of gender diversity and intellectual capital on GRI-based SPD. Further, extant content analysis studies provide evidence from other contexts other than Uganda (e.g.…”
Section: Introductionmentioning
confidence: 99%